PENGARUH MULTIMEDIA INTERAKTIF CANVA DAN WORDWALL TERHADAP HASIL BELAJAR IPA MATERI EKOSISTEM SISWA SEKOLAH DASAR - Syahvella Octasetya, Minanda; Rizkya Putri Setyarini; Amelia Kholifah; Dwi Galuh Nofiyanti; Ayu Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the use of interactive multimedia based on Canva and Wordwall on the learning outcomes of science on ecosystem material of third-grade students of SDN Soco 2. This type of research is quantitative research with One Group Pretest-Posttest Design. The population in this study were all third-grade students of SDN Soco 2 with a sample of 19 students selected using saturated sampling techniques. Data collection techniques were carried out through tests in the form of pretest and posttest questions. Data analysis used descriptive statistics, Shapiro-Wilk normality test, and paired samples t test hypothesis test with the help of SPSS version 20. The results showed an increase in the average student learning outcomes from 68.53 in the pretest to 77.37 in the posttest with a difference of 8.84 points. The results of the paired samples t test obtained a significance value of 0.001<0.05, so it can be concluded that there is a significant influence of the use of interactive multimedia based on Canva and Wordwall on the learning outcomes of science on ecosystem material of third-grade students of SDN Soco 2.